Normy bezpieczeństwa systemów informatycznych - Mazur, Hanna; Mazur, Zygmunt; Mendyk-Krajewska, Teresa (Information Systems Security Norms, 2005)
The work presents Polish and international norms for the security of electronic, written and spoken information and information computer systems. We also analyse the aspect of the security level in the context of carrying out audits.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 424-434